Trends in ecosystem and health responses to long-range transported atmospheric pollutants : Convention on long-range transboundary air pollution. International cooperative programme on assessment and monitoring effects of air pollution on rivers and lakes - Seidling, Walter; Waldner, Peter; Marchetto, Aldo; Hansen, Karin; Potočić, Nenad; Timmermann, Volkmar; Trotzer, Serina; Jonard, Mathieu; Fürst, Alfred; Rautio, Pasi; Schaub, Marcus; Haeni, Mathias; et al. (Norwegian Institute for Water Research, NIVA, 2015)
The aim of this trend report is to assess the effectiveness of air pollution policies under the Convention on Long-range Transboundary Air Pollution (LRTAP), and to document progress and identify remaining challenges. Trends in environmental and health responses to long-range transported air pollution are presented, primarily focusing on 1990 to 2012 and on Europe, with additional data from North America and the Arctic region. Air pollutants included in the report are sulphur and nitrogen as acidifying agents, nutrient-nitrogen, ground-level ozone, particulate matter (PM), heavy metals and persistent organic pollutants (POPs). The results are from work done under the bodies of the Working Group on Effects of the LRTAP Convention, i.e. ICP Integrated Monitoring, ICP Forests, ICP Materials, ICP Modelling and Mapping, ICP Vegetation, ICP Waters, JEG Dynamic Modelling and the Task Force on Health. The European Monitoring and Evaluation Programme (EMEP) and the Arctic Monitoring and Assessment Programme (AMAP) also contributed.
Folia element contents, p. 31-32 ; Norwegian Institute for Water Research, Report No. 6946-2015, revised 21.04.2016
Keywords: biological recovery; air pollution; forests; trends